The Identity-Based Habits Laws to Analyze the Students’ Reading Habits at University - Marianda Arwinda, Desy; AM, St Asriati; Ariana (Institut Agama Islam Negeri Palopo, 2024)
This research aimed to analyze the students’ reading habits through The Identity-Based Habits Laws at Universitas Muhammadiyah Makassar. The data were collected at Universitas Muhammadiyah Makassar. This research used a descriptive qualitative method, and the instruments used an interview. The findings of this research show that students have diverse reading habits, preferences, and time spent. They prefer apps, textbooks, and various genres. Distractions like cellphone interference and notifications can hinder reading experiences. Consistent reading habits, schedules, and discipline were essential. The result of the interview of this research showed that The Identity-Based Habits Laws at Universitas Muhammadiyah Makassar outlines four key habits to improve students' reading habits: making reading obvious, making reading attractive, making reading easy, and making reading satisfying. These habits involve reducing distractions, engaging in conversations with friends, setting simple goals, and finding books that help overcome life's challenges, focusing on genres like novels, fiction, fantasy, action, crime, dark romance, and self-development.